Desenvolvimento de produto tipo hambúrguer à base de cogumelos do gênero Pleurotus - Jesus, João Paulo Furlan de [UNESP] (2015)
The consumption of alternative foods, rich in protein and dietary fiber as well as low in calories and lipids like mushrooms, grown on a global scale with increasing public concern about food and health issues. Despite the global growth, the consumption of mushrooms is still low in Brazil due to cultural factors related to lack of knowledge in cooking procedures for consumption. Thus, the work aimed to develop an alternative product to conventional hamburger, based on fresh Oyster mushrooms (FUNGIBURGER) and compare with beef burger samples (HAMBURGER) and soya burger samples (SOJABURGUER) purchased in local markets at Botucatu, SP. Through microbiological analyzes the FUNGIBURGER was safe for consumption. The highest average for overall acceptability (7,7a), purchase intent (4,3a) and preference order (233a ) were obtained by FUNGIBURGER, followed by HAMBURGER (7,3a ; 2,9b; 260a ) and SOJABURGER (5,8b; 2,7c; 407b) samples. It was observed a high correlation between the frequency of the results observed for the sample FUNGIBURGER and IDEAL preference for soft appearance (75 and 80%), mild taste (72 and 69%), savory (60 and 61%), mushroom flavour (59 and 51%), plea s ant ta s te (58 and 54%), good color (56 and 3 0%), rough exterior (5 2 and 5 5%), juicy (3 5 and 4 1%), well done (29 and 37%), da rk (27 and 37%). Regarding the chemical compos ition, after cooking the FUNGIBURGER showed the highest moisture content (62.2%) and crude fiber (3 .3%); the lower crude protein (8.3%) and total caloric value (114,0Kcal / 56g); intermediate levels of lipids (14.0%) and total carbohydrates (11.1). The higher lipid content, total carbohydrates and total energy intake were observed in HAMBURGER (19.7% and 155,4Kcal / 56g) and SOJABURGER (36.9% and 174,2Kca l / 56g) samples after cooking respectively. Through the sensory results... (Complete abstract click electronic access below)